2017
DOI: 10.1007/s00280-017-3353-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in patients with advanced biliary tract cancer treated with first-line gemcitabine plus cisplatin: retrospective analysis of 740 patients

Abstract: Our retrospective analysis of a large number of patients in a real-world setting found comparable efficacy outcomes to the ABC-02 trial. The prognostic factors identified here may help to predict clinical outcomes and design future clinical trials for advanced BTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 16 publications
8
60
2
Order By: Relevance
“…9,12,13 However, it has not been evaluated before in prognostication of advanced/ metastaic disease status except in one study which inculded all biliary tract malignancies. 14 In this study, there were about 25% GBC patients and the analysis was not done for these patients separately. In our study, we could not find any significant association between the presence of elevated levels of CA 19-9 and survival.…”
Section: Discussionmentioning
confidence: 96%
“…9,12,13 However, it has not been evaluated before in prognostication of advanced/ metastaic disease status except in one study which inculded all biliary tract malignancies. 14 In this study, there were about 25% GBC patients and the analysis was not done for these patients separately. In our study, we could not find any significant association between the presence of elevated levels of CA 19-9 and survival.…”
Section: Discussionmentioning
confidence: 96%
“…The median OS of patients with unresected nonmetastatic disease without and with chemotherapy (6.7 and 9.9 months) and of patients with metastatic disease without and with chemotherapy (2.8 and 8.2 months) are not in line with results from previous trials. The median OS of unresected biliary tract cancer is typically reported between 8.1 and 12.7 months [7,27,28]. Obviously, patients selected for clinical trials represent a subset of the total population with better performance status and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with advanced BTC, the phase III ABC-02 and ABC-06 trials showed the clinical efficacy of gemcitabine plus cisplatin (GemCis) and oxaliplatin plus fluoropyrimidine (mFOLFOX) as first-line therapy and second-line therapy, respectively [5,6]. However, the survival outcomes remain dismal with a median overall survival (OS) of < 1 year, and none of the targeted agents have been approved for treatment of BTC [7][8][9].…”
Section: Introductionmentioning
confidence: 99%